Analisis Pemberdayaan Staf dalam Proses Pengambilan Keputusan dan Pengaruhnya Terhadap Produktivitas Organisasi Pada Sekretariat Daerah Kota Tomohon - Plangiten, Novva Novita (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: Leadership is the one of the important things in organization. It will work by cooperating leader and staff to reach many goals planned. Facts show that existency of the staff is less concerned. They are just as the tools of organization. This research using correlation method. Data is collected by using quetionaires and interviews. Respondent are 50 employees worked at the Secretary Office of Tomohon City. The conclusions are: (1) Staff empowerment correlates significantly with the organization productivity at 0,4761. (2) Decision making process correlates significantly with the organization productivity at 0,2704. (3) Staff empowerment correlates significantly with the decision making process ar 0,49. (4) Staf empowerment and decision making process simultancy correlates with the organization productivity at 0,4790. It means organization productivity improvement is influenced by the staff empowerment and decision making process. Based on these results, it is suggested that the government of Tomohon City for effective empowerment of staff in the decision making process needs to be applied with the best principles of complete staff work (completed staff work). Because with this method is the responsibility of staff to help make things easier for the leadership decision will be greater. Keywords : staff empowerment, decision making and organization productivity